Compact Models and Measurement Techniques for High-Speed Interconnects - Sharma, Rohit; Chakravarty, Tapas; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Compact Models and Measurement Techniques for High-Speed Interconnects provides detailed analysis of issues related to high-speed interconnects from the perspective of modeling approaches and measurement techniques. Particular focus is laid on the unified approach (variational method combined with the transverse transmission line technique) to develop efficient compact models for planar interconnects. This book will give a qualitative summary of the various reported modeling techniques and approaches and will help researchers and graduate students with deeper insights into interconnect models in particular and interconnect in general. Time domain and frequency domain measurement techniques and simulation methodology are also explained in this book.
Introduction to interconnects -- Necessity for modeling of interconnects -- Review of analytical models -- Numerical techniques and simulation approaches -- Summary.
Keywords: Engineering; Logic design; Systems engineering; Engineering; Circuits and Systems; Logic Design; Electronic Circuits and Devices; Circuits and Systems